Concurrent esophageal squamous cell carcinoma with gastric mucosa-associated lymphoid tissue lymphoma: a case report - Xu, Ting; Luo, Shuai (Frontiers in Oncology, 2025)
BackgroundDouble primary malignant tumors are infrequently encountered, with esophageal squamous cell carcinoma (ESCC) co-occurring with malignancies in other organs, representing a rare clinical entity. The concomitant presence of ESCC and lymphoma is even more uncommon, posing substantial diagnostic and therapeutic challenges.Case demonstrationA 76-year-old Han Chinese man presented with dizziness, dysphagia, and vomiting. Computed tomography suggested a potential esophageal neoplasm. Gastroscopy identified an ulcerated esophageal mass, accompanied by altered gastric body morphology and branching changes. Histopathological examination of biopsied esophageal and gastric mucosa confirmed ESCC concurrently with gastric mucosa-associated lymphoid tissue (MALT) lymphoma. The patient declined surgical intervention and succumbed 13 months after diagnosis.ConclusionsThe simultaneous occurrence of ESCC and gastric MALT lymphoma remains exceedingly rare. In ESCC cases, the potential for coexisting malignancies in the pharynx, stomach, or other sites warrants consideration. This report documents the first known case of ESCC coexisting with gastric MALT lymphoma, contributing to the current understanding of diagnosis and management strategies in lymphoma-associated ESCC cases.